EPIDEMIOLOGICAL ANALYSIS OF THE HUMAN IMMUNODEFICIENCY VIRUS (World Bulletin of Public Health, 2023)
conduct an epidemiological analysis of the incidence of human immunodeficiency virus in the Republic of Uzbekistan and improve its prevention.
Keywords: HIV infection; analysis; morbidity; distribution